2016
DOI: 10.1021/acs.nanolett.6b01805
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation Driven Conductive Na2Ti3O7 Nanoarrays as Robust Binder-Free Anodes for Sodium-Ion Batteries

Abstract: We present a general and rational approach to fabricate highly accessible and affordable sodium-ion battery anodes by engineering three-dimensional hydrogenated Na2Ti3O7 nanoarrays supported on flexible Ti substrates. The hydrogenated Na2Ti3O7 nanoarrays exhibit desirable properties for sodium storage, such as high surface area, high electrical conductivity, and Na(+) diffusivity. The as-obtained nanoarrays demonstrate remarkably stable and robust Na-storage performance when tested as binder-free anodes for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 45 publications
6
188
0
Order By: Relevance
“…The width of Na 2 Ti 6 O 13 microrod was wider than that of Na 2 Ti 3 O 7 . By careful comparison, it was found that the widths of two phases were much wider than that of the previous published paper,24, 34, 35, 36 which may hinder the bulk Na + diffusion and result in a pseudocapacitive phenomenon. The selected area electron diffraction (SAED) pattern of Na 2 Ti 6 O 13 exhibited a monoclinic characteristic spot pattern and proved that the phase was single crystalline (Figure 2b).…”
mentioning
confidence: 69%
“…The width of Na 2 Ti 6 O 13 microrod was wider than that of Na 2 Ti 3 O 7 . By careful comparison, it was found that the widths of two phases were much wider than that of the previous published paper,24, 34, 35, 36 which may hinder the bulk Na + diffusion and result in a pseudocapacitive phenomenon. The selected area electron diffraction (SAED) pattern of Na 2 Ti 6 O 13 exhibited a monoclinic characteristic spot pattern and proved that the phase was single crystalline (Figure 2b).…”
mentioning
confidence: 69%
“…The apparatus used for PLD was described elsewhere [11]. A 355 nm laser beam from Q-Switched Nd:YAG laser (Spectra Physics GCR-150) with a pulsed repetition rate of 10 Hz and a pulsed width of 5 ns was focused onto the SbSn-P target, and the laser intensity was about 2.5 J cm -2 .…”
Section: Methodsmentioning
confidence: 99%
“…hard carbon etc.) [6][7][8][9] and titanium-based intercalation compounds [10][11][12][13]. However, these materials suffer from relatively low specific capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that there is a strain caused by volume change during sodiation process, which can be partially alleviated by the hollow structure. [36,37] As compared to the hollow spheres, thanks to the prolonged length and the consequently high length-to-diameter ratio, the 1D hollow structured anodes, for example, nanotubes, possess extra advantages of good conducting connectivity and better structural stability. Thanks to the good connectivity of tubes and different modifications as shown in the scanning and transmission electron microscope (SEM and TEM) images, a capacity retention of over 90% after 10 000 cycles was achieved, demonstrating their excellent stability ( Figure 1D-F).…”
Section: Simple Hollow Structuresmentioning
confidence: 99%